الرؤية الانتمائية عند طه عبد دالرحمان - ياحي ام السعد; اشراف: بوزبرة عبد السلام (جامعة محمد بوضياف -المسيلة, 2025)
الملخص يتمحور موضوع البحث حول الدراسة التحليلية للفلسفة الائتمانية عند طه عبد الرحمان كمشروع ومنهج فلسفي ونقدي يسعى طه عبد الرحمان من خلاله الى إعادة الصلة بين الاخلاق والدين من جهة وإعادة النظر في الحداثة الغربية من جهة أخرى وذلك من اجل تجديد الفكر الديني الإسلامي وبعث روح الابداع في الفلسفة العربية الاسلامية. الكلمات المفتاحية : طه عبد الرحمان، الفلسفة الائتمانية، الأخلاق، الدين، السياسة ، العلمانية، العنف . Abstract : The research topic revolves around an analytical study of Taha Abdel Rahman's philosophy of trust as a philosophical and critical project and approach. Through this approach, Abdel Rahman seeks to reconnect ethics and religion, on the one hand, and to reconsider Western modernity, on the other. This is done in order to renew Islamic religious thought and revive the spirit of creativity in Arab-Islamic philosophy. Keywords: Taha Abdel Rahman, credit philosophy, ethics, religion, politics, secularism, violence.